AN ACCESSORY FISSURE AND LOBE OF THE LEFT LUNG: CASE REPORT - Mustafa, Dr. Amal Yousif Ahmed Elhaj; Elamin, Dr. Asma Mohammed (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Anatomical variations of the lung lobes and fissures are very common. They have been described by many authors, using imaging techniques, fewer studies were done using gross anatomy. The left lung classically has one fissure, the oblique fissure and two lobes namely the upper and lower lobes. In the present case, we report a variant oblique fissure of left lung. Such abnormal fissures are clinically important for identifying broncho-pulmonary segments.